Analysis Of Microbial Culture Learning: Understanding The Relationship Between Technical Competence And Students' Perspectives At Dharmawangsa University, Medan - Afriani, Dwi Tika; Rofieq, Ainur; Huda, Atok Miftachul; Eriyanti, Ribut Wahyu; Hasruddin, Hasruddin (Universitas Labuhanbatu, 2024)
This study examines the relationship between test scores and students' perceptions of learning microbial cultures. The objectives of the research were to determine how students' technical skills correspond with their subjective perceptions of difficulty in various aspects of learning, and to identify the most difficult aspects of learning microbial cultures. Data were collected through tests and questionnaires administered to microbiology practicum students. Analysis revealed a significant correlation between test scores and student perceptions in most aspects of learning, but with variation between aspects. Aspects of basic microbial culture concepts showed a positive correlation, suggesting that students with a strong understanding of the concepts perceived less difficulty. In contrast, bacterial inoculation techniques showed a negative correlation, indicating a mismatch between technical ability and perceived difficulty. The analysis provides a comprehensive view of the factors influencing the learning of microbial culture. The results show that students perceive bacterial inoculation techniques as the most challenging aspect, despite moderately skilled students demonstrating adequate technical ability. Potential sources of technical complexity in the inoculation process, such as steps requiring precision and access to hands-on equipment, contribute to students' perceived difficulty. Although the relationship between test scores and student perceptions of microbial culture learning has been explored in this study, additional research is needed to delve deeper into the complex factors that contribute to this relationship